(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
In the history of Uzbek literature of the 20th century, the creative activity of writer Shukur Kholmirzayev, who raised Uzbek storytelling to a new level, is highlighted.